Do livro à televisão: o romance O tempo e o vento na minissérie da TV Globo - Guimarães, Magda de Oliveira (2014)
Based on the study of the book O Tempo e o Vento , by Erico Verissimo, the present dissertation analyses and discusses the transcreation of this book, a printed media, into an audiovisual media, the homonymous television adaptation made by TV Globo broadcasting company in 1985. This subject of study is placed in the Interdisciplinary Program in Contemporary Culture and Arts, for it employs knowledge of diverse areas, such as written language and audiovisual media, and evaluates the transposition of erudite culture (the book) into mass culture (the television). This study evaluated the first ten years of TV Globo s broadcasting of mini-series (1982-1991), establishing the themes of the TV shows regarding the current Brazilian cultural problems and the reasons behind the choice of a given theme for production. The historical issues presented by the TV show and the adapted book were studied, and the different issues involved in their fruition were observed, such as the amount of time spent by viewers, the place and time, the prior formation (study level, and the preference for passively watching the TV show or actively reading the book). The mini-series chosen was the first big production made by TV Globo in order to celebrate its 20th anniversary: entitled O Tempo e o Vento , this adaptation, homonymous to the trilogy written by Verissimo, depicts the first volume of the trilogy, called O Continente launched in 1949 by Globo Publishing House. One chapter of the book Ana Terra was selected, which is about the story of Pedro Missioneiro and Ana Terra. Using tenets of content analysis developed by Laurence Bardin, two ambivalent nuclei were chosen (life and death), from which 85 passages of the written text containing behaviors and feelings corresponding to the nuclei were selected. Based on these data, the inclusions and exclusions, artistic creation and differences between the original and the adapted work were analyzed. It was seen that the items that presented more occurrences were fear (18), which belongs to the death nucleon, with 36 inclusions in the mini-series, as opposed to life, which had only 26 inclusions, happiness being the item with more occurrences (only 6). Therefore, the adaptation maintained the climate of tension similar to the book, and a harmonious and edifying climate was not found.